Hydrological dataset of a sub-humid continental plain basin (Buenos Aires, Argentina) - Zabala, María Emilia (2020)
The Chaco-Pampean Plain (Argentina) is the strongest eco- nomic region and the most inhabited in the country, comprising approximately 66% of the country’s population (26,500 million) [1] . In this region, surface slopes are very low ( < 0.1%) and due to the current climatological features, floods and droughts alternate over time. Salinity and alka- linity of water and soil increase towards the flattest sector of the basin, as well as the contents of arsenic and fluo- ride, which restrict their human use. Worldwide, population growth and global warming, in addition to political decisions, are leading to abrupt land use changes. Under this premise, identifying and quantifying the hydrological processes that control water quantity and its chemical quality become an imperative task [2] . This data article provides a long-term hy- drological dataset from a sector of the Chaco-Pampean Plain, the Del Azul creek basin. Hydrological data such as flow rates and piezometric levels, and physical–chemical (i.e., major and minor solutes, and trace elements) and isotopic ( δ18 O, δ2 H; and D -excess) data from rainwater, surface (creek and wet- land) and groundwater (at two depths) are available. Rain- water samples are derived from three precipitation collec- tors installed at different altitudes (monitoring period: 2010–2019; n = 57). Surface water samples were collected at three sampling sites located along the Del Azul Creek and six wet- lands (monitoring period: 2018–2019; n = 12). Groundwater samples were collected from 17 piezometers with depths ranging between 3 and 10 m, and from 12 piezometers of 30 m depth, all located throughout the entire basin (moni- toring period: 2018–2019; n = 115). Sampling campaigns were performed during the austral dry (summer) and wet (spring) seasons. This dataset provides useful information to under- stand a) how water moves from recharge to discharge areas, b) how water acquires salinity, and c) how particular solutes of concern, such as arsenic and fluoride, are distributed in space and time across in an extensive plain.